Enviromental Health Officer Emergency Preparedness and Response on Ebola Outbreak (Case of Enviromentalist at IjebuOde, Ikenne, Odogbolu and Sagamu L.G.A) Ogun State - Agboola H.O , Agboola H.O; Rosiji , C.O. (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
Ebola Virus Disease (EVD; also known as Ebola Haemorrhagic Fever (EHF)) is a disease of humans and other primates caused by Ebola Viruses. This study is to determine the emergency preparedness and response in Ebola Viral Disease outbreak by Environmental Health Officers in selected Local Government Areas of Ogun State (Odogbolu, Ijebu- Ode, Sagamu, and Ikenne Local Government Areas). Two Hundred (200) Environmental Health Officers present in the population area were selected using simple random sampling technique. Descriptive statistics of frequency count and percentage table was used to show the demographic aspect of the data while inferential statistics of chi-square was used to analyse the hypotheses stated in the study. The results of the findings made it clear that the respondents were prepared in responding and handling of Ebola Virus Disease outbreak in the study area. In conclusion, the researchers recognize the heroic efforts of Environmental Health Officers both national and international, who have sacrificed their lives in the effort to stem the spread of disease. It was recommended that there should not be a general ban on both local and international travel and trade; restrictions regarding the travel of EVD cases and contacts should be implemented. Also, International bodies should fully support the Governments of the countries and member states of the United Nations (UN) in coordinating with regard to international assistance in response to the Ebola crisis.